Implementation of Google Cloud in Business to Business Tanda Tukar Faktur Application - Benny Kurniawan; Radius Tanone (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2021)
Alfamart is a company engaged in retail. Companies involved in the retail sector are certainly inseparable from buying and selling products, and every transaction that occurs will be detailed in the invoice exchange. The problem that arises is because Alfamart wants to accommodate the electronic invoice exchange process. Therefore, Alfamart built a B2B TTF application that can accommodate the electronic invoice exchange process and help its accounting management. The application is made using the Research and Development method because it can address urgent needs and has a high validation value. It is built using the Flask framework and is integrated with Google Cloud to overcome application deployment speed problems and be more flexible. In addition, the implementation of Optical Character Recognition using Google Vision is used to validate uploaded invoice files. This study's results are in the form of a B2B TTF application that can make it easier for users to exchange invoices. The results of using Google Vision have a relatively high percentage of 77%. The B2B TTF application uses the Flask framework and is integrated with Google Cloud, which can assist users in the process of exchanging invoices electronically.